ANALYSIS OF SMALL-SCALE MINING IN MINERAL AND COAL MINING LAW NUMBER 4/2009 (INPUTS FOR FORMULATION OF IMPLEMENTING REGULATION) - BAMBANG YUNIANTO (Puslitbang tekMIRA, 2009)
Law Number 4/2009 on Mineral and Coal Mining has been approved by the DPR (the Indonesian Parlia- ment) and issued by the government on January 12, 2009. Explicitely, small-scale mining is regulated by the law and the upcoming governmental decree that regulates its implementation to be issued in 2010, followed by the ministrial decree and regional regulation. In the meantime, illegal mining activites (PETI - Pertambangan Tanpa Izin) reported everywhere in Indone- sia. It reminds us on the case of tremendous environmental disaster due to illegal gold mine in Central Kalimantan, inconventional tin mine in Bangka Belitung, illegal coal mine in South Kalimantan, and illegal mine of industrial mineral (C Group minerals) in all areas in Indonesia. The current question is will those dissaters happen again and can the Law Number 4/2009 prevents it from happening? Analysis on the law identifies that the law needs to be clarified with implementing regulations that, among others, regulate the small-scale’s mining area, small-scale mining authorization, the right and responsibility of mining authorization holder, transfer of authority to head of district, the right of mining authorization holder over the land, etc.